Analysis and restraining of eddy current damping effect in linear voice coil motor. Issue 5 (25th February 2020) - Luo, Ciyong; Zhao, Rui
Abstract : In the case of designing linear voice coil motors (LVCMs), the aluminium tube is usually used to support and fix the windings. Due to the high‐speed linear reciprocating motion, the eddy‐current damping force in aluminium tube has a large effect on the dynamic characteristic of LVCMs and weakens the resultant force. In this study, an LVCM with forward winding is studied. The cause of eddy current damping force in the original structure of the aluminium tube is analysed, and the corresponding mathematic model is established which is verified by finite element method. To restrain the damping effect, three restraining measurements have been discussed. Then a novel structure of aluminium tube with axial slits and ribbed stiffeners is proposed according to the simulation analysis. During the experimentation process, the mover resultant force is replaced with its acceleration. Results show that the mover acceleration of LVCM with stiffened aluminium tube is bigger than that of the initial one. Hence the resultant force of the proposed structure is improved effectively and the new structure has a good inhibition effect on eddy‐current damping effect.